Prevalence of Sydenham’s chorea in patients with Acute Rheumatic fever in Nepal - Regmi, PR; Shrestha, A; Khanal, HH; Nepal, BP; Chapagain, P (Nepalese Heart Journal, 2013)
Background Sydenham’s Chorea (SC) is a major manifestation of acute rheumatic fever (ARF) and is the only evidence of ARF in approximately 20% of cases. There are no published reports on prevalence of SC in patients with ARF in Nepal. Objectives This retrospective study was done to find out the prevalence of SC in patients with ARF in Nepal. Methods Four years data of 672 patients with ARF from the RF/RHD registry of National RF/RHD prevention & control programme launched by Ministry of Health and Population & Nepal Heart Foundation in 32 hospitals throughout Nepal were analyzed. Results Prevalence of SC as a major manifestation of ARF in Nepalese patients was found to be 3.87%. Females were mostly affected with a female-to-male ratio of 3:1. Patients of age group 10-15 years were affected the most. SC was the third most common manifestation of ARF after Arthritis and Carditis. DOI: http://dx.doi.org/10.3126/njh.v9i1.8345 Nepalese Heart Journal Vol.9(1) 2012 pp.30-32